Towards A More Blended Language Learning With Web 2 - Elverici, Sibel Ergun (WILEY, 2025)
While educational environments are swiftly evolving to embrace and offer increased accessibility to technological resources, the inquiry into the appropriate utilisation of Web 2.0 tools in education persists. Thus, this study investigates the efficiency of a blended language learning environment that incorporates Web 2.0 technologies in accordance with a specifically framed instructional design in enhancing English language learning outcomes and social presence. It seeks to explore the impact of incorporating Padlet in English classes on high school students' academic performance and social presence using a mixed-method approach. The standard English test, postinterviews, social presence scale and needs analysis provided the data. Findings indicate that the integration of Padlet into language classes fosters more collaborative language learning settings that result in increased performance in some language skills and social presence. Accordingly, this study is expected to offer valuable insights for educators regarding creating more interactive classroom contexts via Web 2.0 technologies.
Keywords: blended learning; English; performance; social presence; technology integration; Web 2.0; ONLINE; COMMUNITY; FRAMEWORK; EDUCATION; MEDIA; Education & Educational Research